Stability of iron-bearing carbonates in the deep Earth’s interior - Valerio Cerantola (Nature Portfolio, 2017)
Carbonates are shown to exist in the lower mantle as seen in diamond inclusions, but thermodynamic constraints are poorly understood. Here, the authors synthesise two new iron carbonate compounds and find that self-oxidation-reduction reactions can preserve carbonates in the mantle.